Toward satellite-terrestrial integration: 6G cloud-fog collaborative self-organizing network - PENG Mugen; YUAN Shuo (Dianxin kexue)
Low earth orbit (LEO) satellite constellations are evolving to support on-board processing, reconfigurable functions, satellite-terrestrial cooperation, and the coordinated execution of multiple tasks, including communication, sensing, navigation, and control. However, LEO satellite networks are constrained by bottlenecks such as inadequate signal processing and computing capabilities of individual LEO satellites and constrained inter-satellite link capacity, necessitating a deep integration with terrestrial mobile communication networks that include extensive cloud-based processing and computing capabilities. Therefore, an innovative architecture for an integrated satellite-terrestrial-based 6G cloud-fog collaborative self-organizing network was proposed and its protocols were discussed, achieving the deep integration of LEO fog-based satellite networks and terrestrial cloud-based communication networks. In addition, key technologies such as integrated communication, sensing, navigation, and control waveform, as well as resource management based on satellite onboard fog processing, along with mobility management and intelligent information processing based on cloud-fog collaboration, were elaborated in detail. In the end, insights into future directions for standardization and hardware experimentation were presented.